2009
DOI: 10.1021/nl803417v
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linking Bi2S3Ultrathin Nanowires: A Platform for Nanostructure Formation and Biomolecule Detection

Abstract: This paper describes the use of chemical cross-linking of ultrathin inorganic nanowires as a bottom-up strategy for nanostructure fabrication as well as a chemical detection platform. Nanowire microfibers are produced by spinning a nanowire dispersion into a cross-linker solution at room temperature. Nanomembranes with thicknesses down to 50 nm were obtained by injecting the nanowire dispersion at the cross-linker-solution/air interface. Furthermore, the sensitivity of the nanowire to amine cross-linkers allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 11 publications
(18 reference statements)
3
63
0
1
Order By: Relevance
“…Nanostructures of this material have attracted much attention due to their potential applications such as in electrochemical hydrogen storage, hydrogen sensors, X-ray computed tomography imaging, biomolecule detection, and as photoresponsive materials [14][15][16][17][18][19]. However, the photocatalytic properties of Bi 2 S 3 have been scarcely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Nanostructures of this material have attracted much attention due to their potential applications such as in electrochemical hydrogen storage, hydrogen sensors, X-ray computed tomography imaging, biomolecule detection, and as photoresponsive materials [14][15][16][17][18][19]. However, the photocatalytic properties of Bi 2 S 3 have been scarcely reported.…”
Section: Introductionmentioning
confidence: 99%
“…They supported this statement by demonstrating, in a separate paper, how the wires could be spun like polymers into solutions of crosslinkers (i.e., these nanowires bind reliably and selectively to amines) to form microfi bers or nanowire mats. [ 2 ] The following year the Ozin lab reported an extensive structural characterization of the Bi 2 S 3 nanowires and concluded that (i) the local atomic structure of the nanowires is indistinguishable from that of bulk Bi 2 S 3 to EXAFS, XANES, and XPS, and that (ii) the binding of oleylamine to the nanowires is dense (more than one amine is coordinating each surface Bi atom, on average) as well as dynamic (the exchange of oleylamine mole cules with the solution is fast). [ 87 ] In 2012, Cademartiri et al reported an extensive characterization of the conformation and growth kinetic of the Bi 2 S 3 nanowires (see Figure 10 b-f).…”
Section: Examples Of Polymer-like Growth Kinetic In Nanowires and Othmentioning
confidence: 99%
“…Thinner structures were studied by Cademartiri et al, 39,40 who synthesized polycrystalline NWs with diameter as small as 1.6 nm. However, the coherence length of such nanostructures was very short (∼2 nm).…”
Section: ■ Introductionmentioning
confidence: 99%